1997
DOI: 10.1212/wnl.49.6.1552
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor and risk of ischemic stroke

Abstract: We carried out a case-control study to determine whether von Willebrand factor (vWF) antigen (and factor VII and tissue plasminogen activator [tPA] antigens) are associated with ischemic stroke. Ninety-five patients with transient ischemic attack or minor ischemic stroke recruited from the Oxfordshire Community Stroke Project and one neurology clinic were compared with 236 controls, group-matched for age and sex, from the same general practitioners as the incident cases. In crude analyses, concentrations of vW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…20 This procoagulatory protein has been associated with each major cardiovascular risk factor, 21,22 as well with stroke in clinic and community-based longitudinal studies. 23,24 The literature on vWF in migraine is sparse. [25][26][27] We had previously found that migraineurs with prior stroke had higher vWF antigen levels than did migraineurs without stroke.…”
Section: Hypercoagulabitymentioning
confidence: 99%
“…20 This procoagulatory protein has been associated with each major cardiovascular risk factor, 21,22 as well with stroke in clinic and community-based longitudinal studies. 23,24 The literature on vWF in migraine is sparse. [25][26][27] We had previously found that migraineurs with prior stroke had higher vWF antigen levels than did migraineurs without stroke.…”
Section: Hypercoagulabitymentioning
confidence: 99%
“…On the other hand, increased levels of vWF, which may be the result of chronic endothelial cell injury, have been associated with atherogenesis, 2 deep vein thrombosis, 3 myocardial infarction, 4,5 and ischemic stroke. 5,6 Therefore, vWF has been proposed as a target for antithrombotic treatment. 7,8 After secretion into plasma, vWF multimers undergo proteolytic degradation; the 250-kd polypeptide subunits are degraded to fragments of 140, 176, and 189 kd 9 by proteolytic cleavage of the peptide bond Tyr842-Met843.…”
Section: Introductionmentioning
confidence: 99%
“…4 The von Willebrand factor (vWF) is synthesized primarily by vascular endothelial cells and promotes platelet adhesion and aggregation, leading to thrombus formation. 1 Increased levels of vWF in stroke patients have been reported in several case-control studies, [5][6][7][8] but prospective studies have been inconsistent, with some showing a positive relationship 9,10 and others showing no relationship [11][12][13][14] between vWF and stroke risk. Fibrin D-dimer is the primary degradation product of cross-linked fibrin and is a marker of activated coagulation and fibrinolysis.…”
mentioning
confidence: 99%